Development of a novel genetic sexing strain of Ceratitis capitata based on an X-autosome translocation - Cáceres, Carlos; Bourtzis, Kostas; Gouvi, Georgia; Vreysen, Marc J B; Bimbilé Somda, Nanwintoum Séverin; Hejníčková, Martina; Marec, František; Meza, José S (Scientific reports, 2023)
Genetic sexing strains (GSS), such as the Ceratitis capitata (medfly) VIENNA 8 strain, facilitate male-only releases and improve the efficiency and cost-effectiveness of sterile insect technique (SIT) applications. Laboratory domestication may reduce their genetic diversity and mating behaviour and hence, refreshment with wild genetic material is frequently needed. As wild males do not carry the T(Y;A) translocation, and wild females do not easily conform to artificial oviposition, the genetic refreshment of this GSS is a challenging and time-consuming process. In the present study, we report the development of a novel medfly GSS, which is based on a viable homozygous T(XX;AA) translocation using the same selectable markers, the white pupae and temperature-sensitive lethal genes. This allows the en masse cross of T(XX;AA) females with wild males, and the backcrossing of F1 males with the T(XX;AA) females thus facilitating the re-establishment of the GSS as well as its genetic refreshment. The rearing efficiency and mating competitiveness of the novel GSS are similar to those of the T(Y;A)-based VIENNA 8 GSS. However, its advantage to easily allow the genetic refreshment is of great importance as it can ensure the mass production of high-quality males and enhanced efficacy of operational SIT programs.
Keywords: mužská infertilita; mužské pohlaví; rozmnožování; Translocation, Genetic; ženské pohlaví; Reproduction; zvířata; Humans; translokace genetická; Infertility, Male; Female; Pest Control, Biological; biologická kontrola škůdců; Ceratitis capitata; lidé; Male; Animals